Extraction, characterisation, and assessment of the antioxidant activity of Salvia officinalis extracts - Jasim , Abdul Razzaq D.; Omran, Zahraa S .; Chiad, Jamal S.; Rahi, Firas Aziz; Hamad, Moamer T.; Mohammed, Sanaa S. (International Journal of Advanced Chemistry, 2023)
One of the biggest and most significant fragrant and medicinal genera in the Lamiaceae family is salvia (sage). Sage infusion can have numerous health advantages, including anti-mycotic, anti-carcinogenic, antidiabetic, antibacterial, antioxidant, anti-inflammatory, and anti-proliferative effects. By lowering free radicals, antioxidants are the chemical compounds that stop or post-pone the oxidation process. Lipid oxidation causes color changes, texture problems, odd flavors, nutrient loss, and the creation of hazardous chemicals. Aim of study evaluation of the activity of Salvia officinalis extracts as antioxidants. Investigated was the chemical detection of active substances. The existence of an active substances and the use of aqueous and alcoholic extracts separately for toxicity test in mice in three concentrations: (10, 20, and 40 %) it was given orally and the dose ranged between (0.1-0.2) ml twice a day. Leave the mice for 72 h with monitoring to determine the toxicity of the extracts or not, and evaluation of oxidative stress efficiency by using the DDPH method. The presence of these compounds in extracts of the sage plant, which are compounds that have an effectiveness against cancer cells, which lies in the removal of free radicals (OH. O) they contribute to protecting cells and tissues from active oxygen, The toxicity test results of the aqueous and alcoholic extract showed that they were free of toxicity after oral dosing of mice, The active compounds in the prepared extracts have different polarity, in addition to the use of two different solvents, (water and ethanol), which lead differing results of the effectiveness of the aqueous and alcoholic extracts as antioxidants compared to the gallic acid. The tests for the detection of the active groups of the extracts showed that they are affected by the nature of the solvent in terms of polarity, which affects the type and concentration of the groups extracted and the nature of the extraction, The toxicity test results showed that the aqueous and alcoholic extracts were non-toxic, the results of the antioxidant activity test showed that the alcoholic extract of the sage plant is more effective than the aqueous extract.